OSTRACODOS DEL OLIGOCENO DEL NOROESTE DE LA PROVINCIA DE SANTA CRUZ, ARGENTINA (Ameghiniana, 2013)
Samples from the Centinela Formation provided few and not well preserved ostracodes. They belong to 23 genera and 28 species. One taxa has previously been proposed: Urocythereis bertelsae Kielbowicz, 1988. Eleven species are questionably placed in their respective genera. All caparaces are moderately to strongly calcified and most of them are ornamented, medium in size and with amphidont hinge type. The studied microfauna suggests a shallow marine environment with moderate energy levels and temperate temperature.